ASIAN AMERICAN-WHITE DIFFERENCES IN THE EFFECT OF MOTHERHOOD ON CAREER OUTCOMES - Greenman, Emily (Work and occupations, 2011)
U.S.-born Asian Americans are unique among American minority groups in that they lack earnings disadvantages relative to Whites with similar education levels. Controlling for education and age, there is little difference in the earnings of U.S.-born Asian and White men, but Asian women have higher earnings than comparable White women. Using data from SESTAT, this study tests the hypothesis that Asian American women's high earnings may result from adjusting their labor supply less than White women in response to parenthood, leading to greater work experience over time. Findings show that Asian American women are less likely than White women reduce labor supply in response to parenthood, and that their resulting greater work experience explains their high rate of earnings growth